Quantifying Impacts of Local Traffic Policies on PM Concentrations Using Low Cost Sensors in Berlin - Sean Schmitz; Alexandre Caseiro; Andreas Kerschbaumer; Erika von Schneidemesser (Aerosol and Air Quality Research)
Abstract Urban air pollution remains a challenge in European cities, despite decades of improvement, especially with respect to recent updates to the World Health Organization’s (WHO) air quality guidelines in 2021. At the same time, a new generation of small sensors for air pollution measurement have opened up new avenues for understanding air pollution in cities. In this study, we use Plantower PMS 5003 sensors to measure PM2.5 alongside three local traffic policies implemented in 2020 and 2021. These measures include a new bike-lane and a temporary community space, as well as the creation of a pedestrian zone through the closure of a street to through-traffic. The measurement campaign used the sensors in both mobile and stationary deployments, utilizing their small size and lower cost to increase spatial and temporal resolution measurements. We calibrate the Plantower sensors using Schmitz et al.’s (2021b) methodology and test three different models: multiple linear regression (MLR), gradient-boosting machines (GBM), and support vector machines (SVM). Results show that sensors are useful for measuring PM2.5. We also find no significant effect of any of the local transport policies on local concentrations of PM2.5, despite previous studies of these policies showing reductions in local NO2 concentrations. This indicates that larger-scale policies tackling urban and regional emissions of PM will be needed to improve PM concentrations and meet WHO standards.